CDKN2A and MTAP Are Useful Biomarkers Detectable by Droplet Digital PCR in Malignant Pleural Mesothelioma: A Potential Alternative Method in Diagnosis Compared to Fluorescence In Situ Hybridisation - Cheng, Yuen Yee; Yuen, Man Lee; Rath, Emma M.; Johnson, Ben; Zhuang, Ling; Yu, Ta-kun; Aleksova, Vesna; Linton, Anthony; Kao, Steven; Clarke, Candice Julie; McCaughan, Brian C.; Takahashi, Ken; et al. (Frontiers in Oncology, 2020)
Background: The diagnosis of Malignant Pleural Mesothelioma (MPM) can be difficult, in part due to the difficulty in distinguishing between MPM and reactive mesothelial hyperplasia (RMH). The tumour suppressor gene, p16(CDKN2A), is frequently silenced by epigenetic mechanisms in many cancers; in the case of MPM it is mostly silenced via genomic deletion. Co-deletion of the p16 (CDKN2A) and methylthioadenosine phosphorylase (MTAP) genes has been researched extensively and discovered to be a highly specific characteristic of MPM. Most studies have used FISH to detect the deletion of p16 and IHC for MTAP as a surrogate. In this study, we aim to investigate and validate an emerging alternative, efficient testing platform, droplet digital PCR (ddPCR), using this particular genetic characteristic of MPM. Methods: This study included formalin fixed paraffin embedded (FFPE) (75) MPM tissue, and normal RMH (10) was collected and used as a control. Additionally, primary MPM cell lines and normal pleural samples were used as biomarker detection controls, as established in our previous publication. All FFPE were processed to isolate the DNA, that was subsequently used for ddPCR detection of p16 and MTAP. FFPE samples were also analysed by FISH for p16 and MTAP deletion, and for MTAP IHC expression. Concordance of IHC and ddPCR with FISH were studied in these samples. Results: Most cases showed a loss of both MTAP and p16 when determined by FISH, with similar results for MTAP IHC. We confirmed that p16 and MTAP are often co-deleted in MPM samples, as determined by FISH and ddPCR. Our results reconfirm that the co-deletion of p16 and MTAP is a frequent occurrence in MPM. In addition, our study indicated that detection by ddPCR shows high concordance with the currently utilised gold standard, FISH. Given that the deletion of both p16 and MTAP have high specificity in the diagnosis of MPM, our in-house designed ddPCR assays for p16 and MTAP are useful in differentiating MPM from RMH. ddPCR detection of these genetic losses can potentially be utilised for the future development of a less-invasive MPM-specific detection technique on MPM tumour tissue DNA.